The Policy of Integration in Developing The Skills of People with Special Needs Through A Professional Didactic Approach â€œAnalytical Field Study on the Reality of Integrated Classes in Azrou Cityâ€ - Siham Zain; SoufianeZerraf; Said Belaaouad; Abderrahimkhyati (Iraqi Journal of Science, 2021)
In view of the importance of the educational act, and the effective role played by the school in building the society on the basis of solidarity and equal opportunities, as well as the rehabilitation of emerging generations to exercise their rights and duties, as well as integration into the world of knowledge, communication and in different social and environmental circles[1]. The process of integrating special needs children, in regular or integrated classes within regular public schools or specialized rehabilitation educational centers, is of great importance to these groups of society, their families and society in general[2]. Based on the above, the research will start by answering the followingquestions: How can the parents of children with special needs consider the educational process offered by the integrated classes? Can they have a different view of the fact that their children are being integrated? To what extent can educational performance of the integrated classes makes change on special needs children and their family environment? Where does the integration approach emerge through the educational process for special needs children? This study was conducted in the integrated classes in Azrou city depending of Ifrane provincial direction (National Education Ministry) in each of the following institutions: Imam Ali bin Abi TalibSchool Abdel Karim El KhattabiSchool Musa binNusairSchool Education section of the regional compound for people in specialneeds. In the period from September 2017 to February 2019 the study was conducted on a sample of special needs parents, as well as a sample of special needs children and on a sample of teachers working in the integrated classes. in this research we have adopted a descriptive analytical approach because it fits the nature of the study, which is classified as part of exploratory studies, where it requires the collection of information and facts on the problem presented by type of special needs and the selection of different samples from parents and the teachers in the integrated classes and children in a difficult situation by conducting interviews based on technical forms, The study showed that the integrated classes of Azrou city have changed the view for the parents about the integration of their children educationally in society according to several variables.